ENHANCING MATHEMATICAL PROBLEM-SOLVING ABILITIES THROUGH THE TGT LEARNING MODEL ASSISTED BY MEDICA - Sari, Siti Mulya; Kironoratri, Lintang; Riswari, Lovika Ardana (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
Based on preliminary study results, it was found that students' mathematical problem-solving abilities were still low. This study aims to determine the improvement of mathematical problem-solving skills through the application of the Teams Games Tournament (TGT) learning model assisted by MEDICA. This research is a quantitative experimental study with a pre-experimental design. The research design used is the one group pretest-posttest design. The population in this study consists of fourth-grade students at SD Negeri Pati Wetan 01, with a total sample of 31 students selected using a census (total sampling) technique. Data collection techniques include interviews, observations, tests, and documentation. Data analysis techniques involve normality tests and N-Gain tests. The N-Gain test analysis results show an overall improvement score of 0.66, which falls into the medium category. Thus, it can be concluded that the use of the TGT learning model assisted by MEDICA can improve students' mathematical problem-solving abilities. These findings indicate that the application of the TGT learning model assisted by MEDICA is effective in enhancing students' mathematical problem-solving skills. This study suggests using the TGT learning model assisted by MEDICA as an effective strategy to improve elementary students' mathematical problem-solving abilities.